CHEMICAL CONSTITUENTS OF THE ROOTS OF FRITILLARIA PALLIDIFLORA - Utegenova Lazzat; Nurlybekova Aliya; Duysebaeva Moldyr; Jenis Janar (Academic Scientific Journal of Chemistry, 2019)
The roots of F.pallidiflora collected in Kazakhstan were investigated for chemical constituent. The quantitative and qualitative analysis of the medicinal plant have been made. Biological active constituents such as organic acid (1.08%), flavonoids (0.17%) together with moisture content (7.13 %), ash (20.796%), and extractives (12.85%) of plant F.pallidiflora were determined. By using the method of multi-element atomic emission spectral analysis in theash of the plantwas found 8 macro-micro elements, in which the main contents were Potassium (440.420 mcg/ml) and Sodium (33.7475 mcg/ml). In addition, twenty amino and eight fatty acids were identified from F.pallidiflora. The results showed that the major contents of amino acids were glutamate (2650 mg/100g), aspartate (1185 mg/100g) and alanine (802 mg/100g), and fatty acids were linoleic (24.2%) and oleic acids (48.4%), respectively.